1297. Characteristics for PrEP Uptake, Retention, and Discontinuation: Data From the ANCHOR Study. (26th November 2018) - Mathur, Poonam; Kattakuzhy, Sarah; Nussdorf, Laura; Hill, Kristi; Silk, Rachel; Gross, Chloe; Akoth, Elizabeth; Sidique, Nadeera; Chaudhury, Chloe; Sternberg, David; Masur, Henry; Kottilil, Shyam; et al.
Abstract: Background: People who inject drugs (PWID) have an increased risk for HIV, and HCV infection may foreshadow HIV acquisition in current epidemics. Studies of PWID have demonstrated a desire to obtain HCV treatment; however, use of pre-exposure prophylaxis (PrEP) in this population has not been well studied. Methods: The ANCHOR study is an ongoing single-center study evaluating treatment of HCV in PWID. Enrolled patients have chronic HCV, opioid use disorder, and inject opioids. Patients are treated with sofosbuvir/velpatasvir and offered PrEP. Patients complete baseline community health worker (CHW)-administered surveys, physician assessment of PrEP eligibility, and are offered PrEP uptake. Results: Of 89 enrolled patients, 49 (55%) met CDC criteria for PrEP, and 21 (24%) patients started PrEP. Reasons for not starting PrEP are in Figure 1. Though most patients are black ( n = 82, 92.1%) and heterosexual ( n = 81, 91%), these patients were less likely to start PrEP ( P = 0.0068 and P = 0.0283, respectively). Baseline interest in starting PrEP was correlated with uptake ( P = 0.0023), however, self-identifying as high-risk for HIV acquisition or meeting CDC criteria for PrEP were not. Though more patients endorsed sharing of injection equipment to a CHW than a physician (17% vs. 7%), endorsement to a physician rather than CHW was associated with starting PrEP ( P = 0.0307). To date, 13 (62%) patients discontinued PrEP, 7 (54%) due to side effects. Conclusion: Preliminary results of the ANCHOR study support that engagement in HCV care provides an opportunity for PWID to participate in PrEP intake; however, we found relatively low uptake in these patients, despite over half meeting CDC criteria. Our findings highlight the importance of counseling by physicians for initiation of PrEP, and suggest that improved communication between CHW and physician regarding risk behaviors could improve uptake. These data also reinforce that patients must be counseled and managed for side effects in order to retain them in care. Given the increasing opioid epidemic in the United States, more consideration needs to be given regarding how to incorporate PrEP into care, and how to effectively target and improve interest in PrEP for high-risk populations with poor uptake, including minorities and PWID. Disclosures: C. Gross, Merck, Pfizer, Johnson and Johnson: Shareholder, stock. E. Rosenthal, Gilead Sciences, Merck: Grant Investigator, Grant recipient.